Locus-Specific Control of DNA Methylation by the Arabidopsis SUVH5 Histone Methyltransferase - Ebbs, Michelle L. (American Society of Plant Biologists, 2006)
In Arabidopsis thaliana, heterochromatin formation is guided by double-stranded RNA (dsRNA), which triggers methylation of histone H3 at Lys-9 (H3 mK9) and CG plus non-CG methylation on identical DNA sequences. At heterochromatin targets including transposons and centromere repeats, H3 mK9 mediated by the Su(var)3-9 homologue 4 (SUVH4)/KYP histone methyltransferase (MTase) is required for the maintenance of non-CG methylation by the CMT3 DNA MTase. Here, we show that although SUVH4 is the major H3 K9 MTase, the SUVH5 protein also has histone MTase activity in vitro and contributes to the maintenance of H3 mK9 and CMT3-mediated non-CG methylation in vivo. Strikingly, the relative contributions of SUVH4, SUVH5, and a third related histone MTase, SUVH6, to non-CG methylation are locus-specific. For example, SUVH4 and SUVH5 together control transposon sequences with only a minor contribution from SUVH6, whereas SUVH4 and SUVH6 together control a transcribed inverted repeat source of dsRNA with only a minor contribution from SUVH5. This locus-specific variation suggests different mechanisms for recruiting or activating SUVH enzymes at different heterochromatic sequences. The suvh4 suvh5 suvh6 triple mutant loses both monomethyl and dimethyl H3 K9 at target loci. The suvh4 suvh5 suvh6 mutant also displays a loss of non-CG methylation similar to a cmt3 mutant, indicating that SUVH4, SUVH5, and SUVH6 together control CMT3 activity.